Representasi Feminisme Liberal dalam Mulan dan The Lord of The Rings: Analisis Dramatistic Pentad - Hutami, Cantika Proborini Sekar; Ari S. Widodo Poespodihardjo (Jurnal Spektrum Komunikasi, 2025)
This research explores the portrayal of feminism in the films Mulan (1998) and The Lord of the Rings: The Return of the King (2003), focusing on how feminist values emerge through the actions and choices of the central female characters and how mainstream fantasy films can reflect and inspire progressive social change in gender norms and roles. Utilizing Kenneth Burke’s Dramatistic Pentad—comprising act, scene, agent, agency, and purpose. This study analyzes key scenes where Mulan defies conscription laws by disguising herself as a man and Éowyn enters battle despite royal prohibitions, examined through the lens of liberal feminism, which emphasizes individual autonomy and equal rights. The findings reveal that both characters challenge patriarchal structures by asserting agency within traditionally male-dominated spheres. Mulan and Éowyn not only achieve personal empowerment but also contribute to collective victories